Development of an Online Radiology Case Review System Featuring Interactive Navigation of Volumetric Image Datasets Using Advanced Visualization Techniques - Yang, Hyun Kyung; Woo, Hyunsik; Jo, Jaemin; Lee, Min Hee; Kim, Bohyoung; Seo, Jinwook; Jung, Ju Hyun; Kang, Heung Sik; Lee, Kyoung Ho (Journal of the Korean Society of Radiology, 2015)
Purpose: To develop an online radiology case review system that allows interactive navigation of volumetric image datasets using advanced visualization techniques. Materials and Methods: Our Institutional Review Board approved the use of the patient data and waived the need for informed consent. We determined the following system requirements: volumetric navigation, accessibility, scalability, undemanding case management, trainee encouragement, and simulation of a busy practice. The system comprised a case registry server, client case review program, and commercially available cloud-based image viewing system. Results: In the pilot test, we used 30 cases of low-dose abdomen computed tomography for the diagnosis of acute appendicitis. In each case, a trainee was required to navigate through the images and submit answers to the case questions. The trainee was then given the correct answers and key images, as well as the image dataset with annotations on the appendix. After evaluation of all cases, the system displayed the diagnostic accuracy and average review time, and the trainee was asked to reassess the failed cases. The pilot system was deployed successfully in a hands-on workshop course. Conclusion: We developed an online radiology case review system that allows interactive navigation of volumetric image datasets using advanced visualization techniques. KCI Citation Count: 1